Intraoperative quality assessment of tissue perfusion with indocyanine green (ICG) in a porcine model of mesenteric ischemia. - Anna Duprée (Public Library of Science (PLoS), 2021)
Background Mesenteric ischemia is a severe and potentially lethal event. Assessment of intestine perfusion is eminently depending on the skills, and the experience of the surgeon. Thus, the therapy is biased by the right evaluation. Aim of this study is to determine the applicability, and the usefulness of fluorescent-imaging (FI) with indocyanine green (ICG) in a porcine model of mesenteric ischemia. Second end-point is the verification of a visual and quantitative assessment tool of the intestinal perfusion. Methods In 18 pigs (54,2 ±2,9kg) an occlusion of a side-branch of the mesenteric artery was performed for 3 (group I, n = 7), 6 (group II, n = 7), and 10 hours (group III, n = 4). After reperfusion a 60 minutes observation period was carried out. 3 regions of interest were defined: ischemic bowel (D1), transitional zone (D2), and non-ischemic bowel (D3). ICG-FI was performed during baseline (T0), occlusion (T1), reperfusion (T2) and after an observation period of 60 minutes (T4). Results All experiments could be finished successfully. ICG-FI was assessed using assessment of background-subtracted peak fluorescence intensity (BSFI), slope of fluorescence intensity (SFI), and a baseline adjusted ratio of both parameters. ICG-FI confirmed loss of perfusion in D1, decreased perfusion in D2, and increased perfusion in D3. After reperfusion ICG-FI increased in group 2 due to a severe tissue damage resulting in a capillary leakage. In group I ICG-FI was equal to baseline values indicating the totally reversible loss of perfusion. Conclusion Using ICG-FI to estimate intestine perfusion after different durations of ischemia is viable using a porcine model of mesenteric ischemia. Even small differences in perfusion can be reliably determined by ICG-FI. Thus, ICG-FI is an encouraging method to evaluate intestine perfusion intraoperatively.